West Nile Virus Positive Blood Donation and Subsequent Entomological Investigation, Austria, 2014 - Kolodziejek, Jolanta; Seidel, Bernhard; Jungbauer, Christof; Dimmel, Katharina; Kolodziejek, Michael; Rudolf, Ivo; Hubálek, Zdenek; Allerberger, Franz; Nowotny, Norbert (PLOS ONE, 2015)
The detection of West Nile virus (WNV) nucleic acid in a blood donation from Vienna, Austria, as well as in Culex pipiens pupae and egg rafts, sampled close to the donor’s residence, is reported. Complete genomic sequences of the human- and mosquito-derived viruses were established, genetically compared and phylogenetically analyzed. The viruses were not identical, but closely related to each other and to recent Czech and Italian isolates, indicating co-circulation of related WNV strains within a confined geographic area. The detection of WNV in a blood donation originating from an area with low WNV prevalence in humans (only three serologically diagnosed cases between 2008 and 2014) is surprising and emphasizes the importance of WNV nucleic acid testing of blood donations even in such areas, along with active mosquito surveillance programs.